Clinical efficacy of dry nutritional treatment products for phenylketonuria in children, adults, and pregnant women: study results - N.A. Semenova; G.V. Baydakova; N.V. Nikitina; V.K. Podolina; E.Yu. Belyashova; V.N. Kuznetsova; E.M. Kochegurova; L.P. Andreeva; O.N. Khaylova; S.I. Kutsev (LCC «Medicine-Inform», 2019)
N.A. Semenova1, G.V. Baydakova1, N.V. Nikitina2, V.K. Podolina2, E.Yu. Belyashova3, V.N. Kuznetsova3, E.M. Kochegurova4, L.P. Andreeva5, O.N. Khaylova5, S.I. Kutsev1 1Research Centre for Medical Genetics, Moscow, Russian Federation 2Clinical and Diagnostic Center "Protection of Health of Mother and Child", Yekaterinburg, Russian Federation 3Orenburg Regional Clinical Hospital No. 2, Orenburg, Russian Federation 4E.M. Bakunina Regional Clinical Perinatal Center, Tver, Russian Federation 5Saratov Regional Children's Clinical Hospital, Saratov, Russian Federation Abstract Aim: to assess the efficacy of domestic nutritional treatment products for phenylketonuria (PKU) in children, adults, and pregnant women. Patients and Methods: 46 patients with verified PKU were enrolled in this open-label multicenter prospective non-controlled study. Patients were allocated to the groups depending on nutritional treatment products which were prescribed according to the Clinical Guidelines of the Ministry of Health of Russian Federation. Clinical efficacy of the products was assessed according to the Good Clinical Practice guidelines based on clinical and laboratory tests. Results: all patients taken nutritional treatment products throughout the study. No dyspepsia, abnormal poop, or allergic reactions were reported. Most patients reported on more pleasant smell and odor of the products as compared with the products taken previously. At baseline, mean phenylalanine levels were within normal limits. After the treatment, phenylalanine levels were stable  in all patients. Clinical and biochemical tests were within normal limits. Conclusion: dry nutritional treatment products are highly effective in children, adults, and pregnant women with PKU. Keywords: phenylketonuria, specialized food, phenylalanine, mixture, products. For citation: Semenova N.A., Baydakova G.V., Nikitina N.V. et al. Clinical efficacy of dry nutritional treatment products for phenylketonuria in children, adults, and pregnant women: study results. Russian Journal of Woman and Child Health. 2019;2(4):355-360.